Efektivitas Sistem Informasi Administrasi Kependudukan Studi Pada Dinas Kependudukan dan Pencatatan Sipil Kota Kendari - Budianingrum, Rica Amalia; Abdullah, Muhammad Zein; Manguntara, La (REZ PUBLICA, 2020)
This study aims to determine and describe the effectiveness of the Population Administration Information System (SIAK) Study at the Population and Civil Registry Office of Kendari City.  The research method used is descriptive qualitative research, a description of the results of interview observations and documentation studies, so as to be able to describe various matters relating to the Effectiveness of Population Administration Information Systems.  The data obtained were analyzed qualitatively and described in descriptive form. The results showed that the Effectiveness of the Population Administration Information System Study in the Population and Civil Registration Office of Kendari City which was reviewed based on the target approach and process approach which included human resources and facilities and infrastructure, (1) the target approach, showed that the achievement of SIAK objectives in the Population Service  and Kendari City Civil Registry is still not maximized because there are still a number of SIAK products that require a long time to publish.  (2) The process approach in terms of human resources management of SIAK in the Kendari City Population and Civil Registry Service shows that it is adequate.  Whereas in terms of facilities and infrastructure for the management of SIAK in the Kendari City Population and Civil Registration Service, this is not yet adequate, because the network as an important factor that supports the smooth operation of SIAK services is still frequently subject to interference, making it one of the obstacles for the Office of Population and Civil Registration of Kendari City.  in providing services to the community.